Berbagi Takjil Sejuta Kebahagiaan: Kolaborasi UKM Jurnalis dan Civitas Akademik STIE Kalpataru dengan Forum GENRE Bogor - Bukhari Muslim (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The community service activity titled “Berbagi Takjil Sejuta Kebahagiaan” (Sharing Takjil for a Million Happiness) was held on March 15, 2025, in the Cibinong area, involving all members of the UKM Jurnalis and the academic community of STIE Kalpataru, with support from the Forum Genre of Bogor Regency. This activity aimed to foster social awareness, strengthen community bonds, and reinforce the role of higher education institutions as agents of social change. By distributing takjil to people traveling before iftar time, the program not only provided direct benefits in fulfilling the needs for breaking the fast but also served as a medium for instilling values of empathy, togetherness, and mutual cooperation. The active participation of all involved parties demonstrated a positive synergy between students, academic staff, and external partners in implementing impactful social programs. Moreover, the success of this event proved that a participatory approach, involving various community elements, can create a warm sense of togetherness and encourage the emergence of similar social initiatives in the future, thereby contributing to the sustainable strengthening of social solidarity and the development of a caring character within the community..